Supporting plant diversity and conservation through landscape planning: A case study in an agro-tourism landscape in Tampusu, North Sulawesi, Indonesia - Fabiola Baby Saroinsong (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Saroinsong FB. 2020. Supporting plant diversity and conservation through landscape planning: a case study in an agro-tourism landscape in Tampusu, North Sulawesi, Indonesia. Biodiversitas 21: 1518-1526. Plants are one of the living elements of a landscape which have dynamic characteristics. In the green/vegetation concept, the diversity of plants becomes vital in landscape planning to articulate the ecological, socio-cultural, and economic aspects in effort to mitigate biodiversity loss. The aim of this study is to illustrate the application of the green concept when planning an agro-tourism landscape in Tampusu region, North Sulawesi, Indonesia which demonstrates the function and utilization of plants in landscape management while paying attention to plant diversity. Data collection was conducted by field surveys, interviews, and literature studies. Data collected and analyzed included the existing conditions of site, site history, planning goal, topography, flora and fauna, climate, existing facilities and utilities, and area management. Based on its function, the green concept in landscape planning in Tampusu agro-tourism grouped plant diversity into four functions, namely production, ecological, architectural, and aesthetic functions. The ecological aspect of plant species selection (both existing species and added species) was based on the consideration of the plant's function in the landscape with special consideration of its contribution to plant diversity and conservation including those considered as endemic species. There are architectural function for examples Goodyera celebica, Racemobambos celebica, Ficus minahassae, Pterospermum celebicum, Diospyros celebica; ecological function for examples F. minahassae, Clerodendrum minahassae, Vatica celebica, Myristica minahassae, Diospyros minahassae, Korthalsia celebica, Licuala celebica, Aquilaria beccariana, Kibatalia wigmanii, Lithocarpus celebica; production function for examples Musa celebica, Musa acuminafe; aesthetic function for examples C. minahassae, Ixora celebica, D. celebica, R. celebica, Phalaenopsis celebensis. This study demonstrates that the application of the green concept in landscape planning can help to translate plant diversity and conservation into management actions, especially in agro-tourism landscape.